2015
DOI: 10.1177/0149206315574596
|View full text |Cite
|
Sign up to set email alerts
|

Training Engagement Theory: A Multilevel Perspective on the Effectiveness of Work-Related Training

Abstract: Training engagement theory provides a multilevel depiction of the antecedents of training effectiveness. By multilevel, we are referring both to the hierarchical nature of constructs-such that employees are embedded in organizations and workgroups-and the temporal nature of processes-emphasizing that macro and within-person processes are not static phenomena. The hierarchical nature of training engagement theory provides a broad account of how processes at various levels in the organizational hierarchy influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 140 publications
(253 reference statements)
6
93
0
3
Order By: Relevance
“…None of the expected clinician practice variables or clinic level variables were associated with dropout. In line with the theory of planned behavior (Ajzen 1991) and training engagement theory (Sitzmann and Weinhardt 2015), older clinicians were more likely to dropout, perhaps reflecting their greater sense of self-efficacy, influence, and perceived self-competence. Older clinicians reported that tracking weekly progress on selected measures was antithetical to how they were trained.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…None of the expected clinician practice variables or clinic level variables were associated with dropout. In line with the theory of planned behavior (Ajzen 1991) and training engagement theory (Sitzmann and Weinhardt 2015), older clinicians were more likely to dropout, perhaps reflecting their greater sense of self-efficacy, influence, and perceived self-competence. Older clinicians reported that tracking weekly progress on selected measures was antithetical to how they were trained.…”
Section: Discussionmentioning
confidence: 82%
“…Contextual factors related to organizational and system goals, demands, and conflicts are key factors often overlooked in efforts to scale up EBPs through workforce training (Sitzmann and Weinhardt 2015). The mental health field could benefit from the business literature to more effectively use training initiatives as a strategy to enhance a competitive edge and to document goal achievement (Sitzmann and Weinhardt 2015). …”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, investing in training promotes the performance of individuals in the organization. 53 Training must be appropriate to the actual business and on the demand of the employers. 54 Also, the pace of global change causes the existing educational needs to change.…”
Section: Discussionmentioning
confidence: 99%